Nurses’s Perception of Leadership Qualities of Ward Incharge at A Tertiary Care Hospital in Nepal: A Descriptive Cross-Sectional Study - Paudel, Sabitri Kumari; Subedi, Krishna Kumari Paudel; Ghimire, Pushpa (Journal of Manmohan Memorial Institute of Health Sciences, 2026)
Introduction: Leadership in hospital settings is central to maintaining a supportive work environment and ensuring quality patient care. Ward in-charges hold key responsibilities in guiding nursing teams, facilitating communication, and promoting coordinated practice. Despite this, limited evidence is available on how nurses in Nepal perceive the leadership qualities of their immediate supervisors. This study was undertaken to explore nurses’ perception of ward in-charge leadership and to determine whether such perceptions vary across selected background characteristics.Method: A hospital-based descriptive cross-sectional design was conducted among 102 nurses working at Kanti Children’s Hospital. Participants were selected using a non-probability convenience sampling technique based on their availability during the data collection period. Data were collected using a structured, self-administered questionnaire consisting of 22 items related to leadership attributes. The internal consistency of the tool was high (Cronbach’s α= 0.936). Data analysis included descriptive statistics and chi-square tests to examine associations. Perception scores were categorized into three levels: negative, fair, and positive.Result: A majority of nurses (57.8%) reported a positive view of leadership qualities, while 40.2% expressed a fair level of perception and a small proportion (2.0%) indicated negative views. Most respondents were within the age range of 21–30 years (51.0%) and had completed bachelor-level education (72.5%). Statistical testing did not show significant relationships between perception levels and variables such as age (p = 0.202), educational status (p = 0.262), work experience (p = 0.640), or ward type (p = 0.708), indicating that leadership perception was similar across theseConclusion: The study found that nurses’ perception of ward in-charge leadership was generally positive. No significant association was observed between leadership perception and selected socio-demographic variables, indicating that perception is more likely influenced by workplace interaction and leadership practices rather than individual characteristics.